2014
DOI: 10.4025/actasciagron.v37i1.17972
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effects on soil chemical attributes and cotton yield from ammonium sulfate and cover crops

Abstract: ABSTRACT. Fertilizer use in no-till systems must be aligned with a correct interpretation of soil chemical attributes and crop demands. The objectives of this work were evaluate the effects of pre-sowing application of ammonium sulfate (AS) and of cover crops on the yields and soil chemical attributes of no-till cotton (Gossypium hirsutum L. r. latifolium Hutch) over two harvesting years. The experiment was arranged in randomized complete block design, with the plots in strips, and the variables were three cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In other studies, Fageria et al (2010) and Ferrari et al (2015) also found the soil pH to decrease with increasing doses of AS fertilizer rates. Ammonium sulphate is an acidic reaction fertilizer and it is stated that it will increase the microflora and Soxidizing bacteria in the soil as a sulphur containing fertilizer, thus accelerating the pH decrease (Lluch and Olivares, 1979;Müftüoğlu and Sarımehmet, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…In other studies, Fageria et al (2010) and Ferrari et al (2015) also found the soil pH to decrease with increasing doses of AS fertilizer rates. Ammonium sulphate is an acidic reaction fertilizer and it is stated that it will increase the microflora and Soxidizing bacteria in the soil as a sulphur containing fertilizer, thus accelerating the pH decrease (Lluch and Olivares, 1979;Müftüoğlu and Sarımehmet, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…An opposite effect was verified when comparing these results with the literature. For example, ammonium sulphate was found to cause a reduction of pH, calcium and magnesium with an increase of the aluminum content (Ferrari et al, 2015). Vol.…”
Section: Resultsmentioning
confidence: 99%
“…Industries have been producing large quantities of nitrogen fertilizers, such as ammonium sulfate, ammonium nitrate, NPK (nitrogen, phosphorus, and potassium), and urea, mainly [27][28][29][30]. However, the most used fertilizer worldwide nowadays is urea due to its high nitrogen content (46%), high solubility, easy application, and its easy production (Figure 1) [6,26,29,31]. Urea is manufactured through a heterogeneous reaction that results in dehydrated urea, which is marketed as granular urea or conventional urea by the agrochemical industries [30,32,33].…”
Section: Fertilizersmentioning
confidence: 99%